Ontology and Integration managing application semantics using ontologies and supporting W3C Standards. - Linthicum, David S.
Many in the world of application integration have begun to adopt the notion of ontology (or the instances of ontology: ontologies). Ontology is a term borrowed from philosophy that refers to the science of describing the kinds of entities in the world and how they are related.